PERENCANAAN STRATEGI MARKETING MIX DALAM MENINGKATKAN KUANTITAS PESERTA DIDIK - Elvis Fernando Tarantein; Bambang Suteng Sulasmono; Ade Iriani (Universitas Negeri Malang, 2019)
Abstract: This study aims to produce a product in the form of a marketing mix strategy plan in increasing the quantity of students in Public Senior High School 5 Tual. This research approach uses a research and development (R & D) approach which consists of 10 (ten) steps that are modified into seven steps, namely potential and problems, data collection, product design, design validation, design revision, product testing, and product revision . Data was collected through observation, interviews, and documentation studies, and FGDs. Data analysis was conducted in two stages, namely qualitative data analysis and SWOT analysis. The results of the study are in the form of a strategic plan developed through R & D steps by first analyzing the potential and problems faced by the school. Next is data collection from the internal aspects and external aspects of the school. After the data is collected then an analysis of internal factors and external factors is carried out through a SWOT analysis. The results of the SWOT analysis are strategies that are in quadrant IV (weakness threats), which support a defensive strategy. Based on the defensive strategy, the product strategy plan is developed by generating strategies namely: (1) development of the school's superior programs; (2) school management planning programming budgeting system (PPBS); (3) structuring school layout; (4) the use of internet media and school exhibitions as a channel for school promotion; (5) recruitment of teachers and other staff according to priorities and propose the addition of teachers intensively to the government; (6) improvement of facilities and infrastructure through collaboration with the government, parents of students, and local entrepreneurs; and (7) planning learning programs that can attract students' attention.Keywords: strategy, marketing mix, increase quantity of students Abstrak: Penelitian ini bertujuan untuk menghasilkan produk berupa rencana strategi marketing mix dalam meningkatkan kuantitas peserta didik di SMA Negeri 5 Tual. Pendekatan penelitian ini menggunakan pendekatan penelitian dan pengembangan (R & D) yang terdiri dari 10 (sepuluh) langkah yang dimodifikasi menjadi tujuh langkah yaitu potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk, dan revisi produk. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi, dan FGD. Analisis data dilakukan dengan dua tahap yaitu analisis data kualitatif dan analisis SWOT. Hasil penelitian berupa rencana strategi yang dikembangkan melalui langkah-langkah R & D dengan terlebih dahulu menganalisis potensi dan masalah yang dihadapi sekolah. Selanjutnya dilakukan pengumpulan data dari aspek insternal dan aspek eksternal sekolah. Setelah data terkumpul kemudian dilakukan analisis terhadap faktor internal dan faktor eksternal melalui analisis SWOT. Hasil dari analisis SWOT berupa strategi yang berada pada kuadran IV (weakness- threats), yang mendukung strategi defensif. Berdasarkan strategi defensif tersebut, produk rencana strategi dikembangkan dengan menghasilkan strategi yaitu: (1) pengembangan program unggulan sekolah; (2) penataan manajemen planning programming budgeting system (PPBS) sekolah; (3) penataan tata ruang sekolah; (4) pemanfaatan media internet dan pameran sekolah sebagai saluran promosi sekolah; (5) perekrutan guru dan staf lainnya sesuai prioritas serta mengusulkan penambahan guru secara intensif kepada pemerintah; (6) peningkatan sarana dan prasarana melalui kerjasama dengan pemerintah, orang tua peserta didik, maupun pengusaha setempat; dan (7) merencanakan program pembelajaran yang dapat menarik perhatian peserta didik. Kata kunci: strategi, marketing mix, peningkatan kuantitas peserta didik